Relationship Between Work Motivation and Health Worker Performance at Kronjo Health Center - Mutmainah, Mutmainah; Vanchapo, Antonius Rino; Lewar, Emanuel Suban Bala; Tusi, Juandri Seprianto; Wang, Yuanyuan; Zou, Guijiao (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Shows that Indonesia is included in the 5 countries with the lowest motivation of health workers, besides Vietnam, Argentina, Nigeria and India. This is due to aspects of fulfilling welfare and information obtained that 175,000 employees 98,512 people or 56% complain about the low incentives received from the institutions where they work. The problem that occurs in health services today is the large number of health workers who do not have high motivation to work due to various factors such as heavy workload, high work risk, domestic and inadequate training programs, but not balanced by good job protection and unsatisfactory wages, not to mention welfare factors and competence factors according to the World Health Organization (WHO). Work motivation and performance of health workers have a very close relationship to performance. Health workers have an important role as executors of health worker services and community health development. This study aims to determine the relationship between work motivation and the performance of health workers at the Kronjo Health Center in 2022. This research is a quantitative study using an analytic survey with a cross-sectional research design. Work motivation in the sufficient category is 16 (38.1%) and the performance of health workers in the good category is 21 (50.2%). this study shows that the p-value = 0.029. this shows that the value of p = 0.029 is still smaller than the critical limit ? = 0.05. There is a significant relationship between work motivation and health worker performance (0.029<0.05).